Indian objects: from artificial to the intangible - Thompson, Analucia (2014)
In this article, we analyze the various meanings ascribed to indigenous objects along the trajectory of the constitution of modern museums, and then we present some considerations on the meanings assigned to them in conceptions of cultural heritage preservationists developed by public policy, specifically by the Instituto do Patrimônio Histórico e Artístico Nacional. We assume that museums were formed as a privileged site of custody of Indian objects, thus expressing the actions, the social practices, the techniques, and the way knowledge used to be and still is constructed and reproduced on items brought to museums. The analysis of meanings and reinterpretations of 'things', that are denominated in certain moments as ethnographic allow deconstruct the idea that objects exist by itself, for example, ethnographic or artistic. We develop, in this sense, an analysis that historicizes process of musealization indigenous objects to understand the shape that nowadays the patrimony of cultural goods of indigenous groups acquires.